Burden of Diseases: Disability Adjusted Life Year and Health Adjusted Life Expectancy in Thailand - Bundhamcharoen, Kanitta; Tangcharoensathien, Viroj (Journal of Health Science of Thailand, 2017)
Disability adjusted life year (DALY) and health adjusted life expectancy (HALE) are vital indicators for health and disease burden measurement. They reflect and measure fatal and non-fatal health outcomes in a comparable single unit. This article describes and explains the methods of the two indicators of burden of disease measurement in Thailand. It briefly discusses the applications of the indicators for decision-making in public health and other public policies in Thailand. The paper demonstrates the figures of the two indicators in 2009 in which the HALE was 65 and 68 years among Thai men and women respectively, compared with life expectancy at birth of 71 and 77 years, while DALY lost was 10.2 million years (male 5.8 and female 4.4 million years). Alcohol dependence and harmful use contributed to 8.7% of total male DALY while diabetes mellitus contributed to 8.6% of total female DALY lost.